2004
DOI: 10.5194/angeo-22-613-2004
|View full text |Cite
|
Sign up to set email alerts
|

Dayside aurora and the role of IMF ∣<i>B<sub>y</sub></i>∣/∣<i>B<sub>z</sub></i>∣: detailed morphology and response to magnetopause reconnection

Abstract: Abstract. We document the detailed spatio-temporal structure of the dayside aurora during intervals of ongoing dayside magnetopause reconnection, primarily during interplanetary magnetic field (IMF) B z ≤0 conditions. The present study is based on ground auroral observations in combination with particle precipitation data from a DMSP spacecraft. We describe auroral forms corresponding to the following particle precipitation regimes identified by Newell and Meng (1994): (i) central plasma sheet (CPS), (ii) prec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
51
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 56 publications
6
51
0
Order By: Relevance
“…One type of transient feature observed in these regions are Poleward Moving Auroral Forms (PMAF). The properties of these PMAF were shown in studies by Shiokawa et al (1996) and Sandholt et al (2004). We can detect these PMAF in our CADI observations.…”
Section: Is the Cusp Much Wider Than 3 Hours?supporting
confidence: 71%
See 1 more Smart Citation
“…One type of transient feature observed in these regions are Poleward Moving Auroral Forms (PMAF). The properties of these PMAF were shown in studies by Shiokawa et al (1996) and Sandholt et al (2004). We can detect these PMAF in our CADI observations.…”
Section: Is the Cusp Much Wider Than 3 Hours?supporting
confidence: 71%
“…but are never seen by the CADI further poleward at Eureka. The study by Sandholt et al (2004), looked carefully at the PMAF occurrence patterns and concluded that the PMAF were on reconnected open field lines.…”
Section: Is the Cusp Much Wider Than 3 Hours?mentioning
confidence: 99%
“…Such a precipitation regime is identified as the open LLBL adjacent the cusp (Newell and Meng, 1998). According to the Lockwood (1997) model newly open field lines are characterized by the disappearance of CPS electrons giving rise to a void regime between the CPS and the LLBL (open field lines), and this model obtained experimental support for cases of southward IMF Sandholt et al, , 2004. Statistically, the open LLBL has sizes on the order of 1 h in MLT and 1 • in MLat (Newell et al, 2004).…”
Section: Discussionmentioning
confidence: 96%
“…It has been noted [e.g., Sandholt et al, 2004] that IMF jB y j/jB z j > 1 conditions favour toward noon propagating auroral events. Likewise in this study, all three event periods identified began during IMF conditions which match this criterion (see Figure 3d).…”
Section: Discussionmentioning
confidence: 99%